Estudo do comportamento físico-mecânico de BTC estabilizado utilizando o planejamento fatorial experimental - Guedes, Luane César Espínola (2018)
Sustainability is nowadays one of the biggest targets to be achieved within civil construction. And this current need to find mechanisms that are good alternatives to reduce major problems of the present time, such as aggression to the environment, the high cost of buildings and the lack of housing is the major justification for studies focused on soil-cement blocks are increasingly sought after. It is in this context that this study is focused, since it is focused on the addition of cement, lime and sisal fiber (together and separated) in the mixture made for the manufacture of compacted earth blocks (CEB) or soil-cement block. These materials are added for the purpose of analyzing and attempting to improve the physical and mechanical properties of the blocks. This analysis was comparative between the results found with those requested by the standards and also served as a database for possible changes to the existing standard on the topic. Although we already have several studies of these additions in blocks of land, there is not yet a study that has been done by statistical planning, as a way to reduce costs and save time, and this was proposed by this work. Tests of resistance to compression, immersion absorption and wetting and drying were done in order to analyze the physico-mechanical behavior of the CEB. After analyzing the results and statistics (through Statistica 7.0), it was concluded that the use of experimental factorial design for resistance to compression was successful in its proposed models, indicating a good quality in relation to its effects and responses, besides statistically significant. The absorption assays are recommended to make tests with more traces and to use the DCCR method (Rotacional Central Composite Design), because possibly for these factors the quadratic model will be statistically significant. In the humidity and drying test, it is advisable to do more tests with more replicates for a better conclusive analysis of the results.